THE EXPANSION OF JEPARA IN THE XVI CENTURY AND ITS POTENTIAL AS A SUPPLEMENT TO HISTORY LEARNING MATERIALS - Hana, Muhammad Yusril; Wijaya, Daya Negri (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2024)
This research aims to develop a history learning supplement on the XVI Century Jepara Expansion. This article is made using historical research methods, in the form of topic selection, source collection or heuristics in the form of "Suma Oriental" by Tome Pires; Jorge de Lemos's chronicle, "Cercos de Malaca"; Diogo do Couto's chronicle "Decada da Asia", source criticism or verification, interpretation, and historical writing or historiography. The results of this research explain the political conditions of Jepara in the 16th century. Jepara is an area on the north coast of Java Island which has a strong sea fleet. This led to several kingdoms asking for help againts the Portuguese, such as the Sultanate of Aceh, the Sultanate of Johor, and the Sultanate of Maluku. The expansion of Jepara in the 16th century was carried out by several Jepara leaders since 1512 during the reign of Pati Unus. Expansion was then carried out again during the reign of Queen Kalinyamat, which was the heyday of the Jepara Kingdom. The XVI Century Jepara Expansion material has the potential to be a supplement to history learning in textbook form, because this material is not discussed in textbooks published by the Ministry of Education and Culture.